Pure cultivation and morphological studies of four chaetoceros taxa from the Coastal Waters of Pahang, Malaysia - Mohd Anuar, Mohd Fuad; Mohammad Noor, Normawaty; Khan Chowdhury, Ahmed Jalal; Yunus, Kamaruzzaman (Penerbit UKM, 2015)
This study was conducted to study the morphological features of species under the genus Chaetoceros isolated from the coastal waters of Pahang, Malaysia. The species were isolated, cultivated and viewed under light microscope (LM) and scanning electron microscope (SEM). Four taxa were successfully isolated and cultivated in pure culture, namely Chaetoceros affinis var. affinis, Chaetoceros affinis var. willei, Chaetoceros anastomosans and Chaetoceros baculites. Both varieties of C. affinis were considered as distinct taxa where both strains can be distinguished based on morphological characteristics. C. affinis var. affinis has a thick cell wall compared with C. affinis var. willei. C. anastomosans has special features including a silica bar on the intersection of setae and the production of mucous. The length of the aperture opening is a new record from this study. The new record obtained for C. baculites includes the size of the aperture, the terminal setae, spinal arrangement, the thinness of the cell wall and the location of the species in tropical waters. Detailed data on each species will be added to the taxonomic information for future studies.